2009
DOI: 10.1200/jco.2008.20.5815
|View full text |Cite
|
Sign up to set email alerts
|

Quality-Adjusted Time Without Symptoms or Toxicity Analysis of Adjuvant Chemotherapy in Non–Small-Cell Lung Cancer: An Analysis of the National Cancer Institute of Canada Clinical Trials Group JBR.10 Trial

Abstract: A B S T R A C T PurposeNational Cancer Institute of Canada Clinical Trials Group JBR.10 demonstrated that adjuvant vinorelbine and cisplatin after resection of stage IB-II non-small-cell lung cancer (NSCLC) improved relapse-free and overall survival. However, many patients either are not referred for chemotherapy or decline treatment. To aid in treatment decision making, quality-adjusted survival estimates of the JBR.10 trial were derived using a quality-adjusted time without symptoms or toxicity (Q-TWiST) ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 17 publications
0
30
0
Order By: Relevance
“…The negative effects on HRQOL are temporary and improvement with a return to baseline function is likely in most patients. A quality-adjusted time without symptoms or toxicity (Q-TWiST) analysis of adjuvant vinorelbine and cisplatin given after resection of stage IB-II NSCLC showed that the adjuvant chemotherapy group had a statistically significant better Q-TWiST in the range of 5 to 6 additional months as compared with an observation-only group of patients [Jang et al 2009]. …”
Section: Lung Cancermentioning
confidence: 99%
“…The negative effects on HRQOL are temporary and improvement with a return to baseline function is likely in most patients. A quality-adjusted time without symptoms or toxicity (Q-TWiST) analysis of adjuvant vinorelbine and cisplatin given after resection of stage IB-II NSCLC showed that the adjuvant chemotherapy group had a statistically significant better Q-TWiST in the range of 5 to 6 additional months as compared with an observation-only group of patients [Jang et al 2009]. …”
Section: Lung Cancermentioning
confidence: 99%
“…This startling fact speaks to the molecular heterogeneity that exists between early stage tumors. Preoperative and adjuvant chemotherapies provide only modest benefits for patients and come with many side effects, thus biomarkers to predict which patients may benefit the most from additional therapies are needed [29] .…”
Section: Prognostic Mirnasmentioning
confidence: 99%
“…Utility values were derived from the literature for patients with and without ACT, SAEs with ACT, and for no cancer as well cancer recurrence [35][36][37][38].…”
Section: Literature-derived Inputsmentioning
confidence: 99%